Community pharmacist-led interventions and their impact on patients' medication adherence and other health outcomes: a systematic review. (21st June 2018) - Milosavljevic, Aleksandra; Aspden, Trudi; Harrison, Jeff
Abstract: Introduction: Medication adherence can be defined as the extent to which one's medication-taking behaviour follows that mutually agreed upon by the prescribing physician. Optimal medication adherence is often deemed crucial for the success of a patient's treatment, as suboptimal adherence may lead to treatment failure and unnecessary medical expenditure. Increasing evidence has highlighted the positive contribution community pharmacist-led interventions can have on improving patients' adherence and health outcomes. Objectives: To provide an overview of the published literature on community pharmacist-led interventions and their effectiveness in improving patients' adherence and health outcomes. Methods: A search strategy was developed, aiming to retrieve published reports of community pharmacy interventions worldwide. Medline, EMBASE, International Pharmaceutical Abstracts, Google Scholar and ProQuest Dissertations and Theses databases were searched. Articles meeting the inclusion criteria were collated, relevant data extracted, and a risk of bias assessment undertaken. Key Findings: Twenty-two studies were included in the analysis, and their outcomes were reported in 26 peer-reviewed journal articles. Community pharmacist-led interventions have been shown to improve patients' adherence and contribute to better blood pressure control, cholesterol management, chronic obstructive pulmonary disease and asthma control. Studies in this review, however, did not report statistically significant effects of interventions on diabetes or depression control. Conclusion: Community pharmacist-led interventions have been shown to contribute to improved adherence and better disease control. Future research should attempt to better understand which particular intervention components make the greatest contribution towards improving adherence and health outcomes, for patients with different medical conditions.